Remarkable Influence of Cobalt Catalysis on Epoxide Ring-Opening with Sulfoxonium Ylides - Jamieson, Megan L.; Brant, Nicola Z.; Brimble, Margaret A.; Furkert, Daniel P. (Synthesis, 2017)
Cobalt demonstrates a remarkable ability to catalytically divert the course of epoxide to oxetane ring expansion via reaction with a sulfoxonium ylide. An expanded survey of transition-metal catalysts has confirmed that cobalt salts uniquely instead deliver homoallylic alcohol products from epoxides, with retention of the original epoxide stereochemistry. The reaction is an unusual example of cobalt-catalysed epoxide ring-opening by a carbon nucleophile. A tandem Corey–Chaykovsky/epoxide olefination sequence giving homoallylic alcohols from aldehydes is further demonstrated along with preliminary mechanistic analysis. This communication summarises current understanding and ongoing studies into this intriguing new cobalt-mediated reactivity.
Keywords: cobalt catalysis; diverted reactivity; epoxide olefination; carbon–carbon bond formation; oxetane; Jacobsen HKR